Diagnosis and treatment of traumatic duodenal rupture in children - Yuanyuan Luo; Xiaobing He; Lanlan Geng; Runxian Ouyang; Yingyi Xu; Yufeng Liang; Jinhui Wu; Hong Zhang; Zhihua Ye; Rongjun Zou; Qiang Wu; Chengwei Chai (BMC Gastroenterology, 2022)
Abstract Background The purpose of this study was to investigate the diagnosis and treatment experience of traumatic duodenal ruptures in children. Methods Clinical data were collected from four children suffering from a traumatic duodenal rupture who were admitted to and treated by our hospital from January 2012 to December 2020. The early diagnosis and treatment, surgical plan, postoperative management, complications, and prognosis of each child were analyzed. The key points and difficulties of the diagnosis and treatment for this type of injury are summarized. Results One child had an extreme infection caused by drug-resistant bacteria, which resulted in severe complications, including wound infection, dehiscence, and an intestinal fistula. One child developed an anastomotic stenosis after the duodenostomy, which improved following an endoscopic balloon dilatation. The other two children had no relevant complications after their operations. All four patients were cured and discharged from hospital. The average hospital stay was 48.25 ± 26.89 days. The follow-up period was 0.5 to 1 year. No other complications occurred, and all children had a positive prognosis. Conclusions The early identification of a duodenal rupture is essential, and surgical exploration should be carried out proactively. The principles of damage-control surgery should be followed as much as possible during the operation. Multidisciplinary cooperation and management are both important to reduce the occurrence of postoperative complications and improve cure rates.